Research Capacity in Higher Education: Theoretical Considerations - Žydžiūnaitė, Vilma; Jurgilė, Vaida; Daugėla, Marius (Pedagogika, 2023)
The aim of this conceptual research was to provide considerations on understanding the essences of institutional research capacity as a notion and as a process within the higher education context and institutional level. The descriptive integrative review with a fivestage integrative review process of 71 scientific resources was implemented and included problem formulation. Research results revealed that institutional research capacity in higher education is a multifaceted concept that has several meanings.